Avaliação nutricional de diferentes variedades de uva (Vitis sp) - Souza, Angela Vacaro de [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Vieites, Rogério Lopes [UNESP] (My University, 2010)
Samples of grapes in point of consumption 'Itália', 'Brasil', 'Rubi', 'Thompson' and 'Niagara Rosada' of the region of Campinas and Jundiaí – SP state - Brazil, were used to evaluate the nutritional quality in peel and pulp, beyond to evaluate the firmness (texture) of the fruits, pH, acidity, soluble solids, relation SS/TA ("Ratio"), content of total solids, humidity (water content), carbohydrates, total and reducing sugar, protein, fiber, fat and ash. From the results, can be conclude that for most of the parameters measured, the fruit peel showed higher levels in relation to pulp and among the varieties tested, the 'Itália' was the one with higher for the most parameters.

Amostras de uva no ponto de consumo ‘Itália’, ‘Brasil’, ‘Rubi’, ‘Thompson’ e ‘Niagara Rosada’ da região de Campinas e Jundiaí – SP foram utilizadas com o objetivo de avaliar a qualidade nutricional em casca e polpa, além de avaliar a firmeza (textura) dos frutos, pH, acidez, sólidos solúveis, relação SS/AT (“Ratio”), teor de sólidos totais, umidade (teor de água), carboidratos, açúcar total e redutor, proteínas, fibras, lipídeos e cinzas. A partir dos resultados encontrados, pode-se concluir que para a maioria dos parâmetros avaliados, as cascas dos frutos apresentaram maiores teores em relação à polpa e entre as variedades analisadas, a ‘Itália’ foi a que apresentou os maiores valores para a maioria dos parâmetros.
Keywords: Grape; Protein; Fiber; Ash; Uva; Proteína; Fibras; Carboidratos